Capillary Liquid Chromatography for the Determination of Terpenes in Botanical Dietary Supplements - Henry Daniel Ponce-Rodríguez; Jorge Verdú-Andrés; Pilar Campíns-Falcó; Rosa Herráez-Hernández (MDPI AG, 2021)
Dietary supplements of botanical origin are increasingly consumed due to their content of plant constituents with potential benefits on health and wellness. Among those constituents, terpenes are gaining attention because of their diverse biological activities (anti-inflammatory, antibacterial, geroprotective, and others). While most of the existing analytical methods have focused on establishing the terpenic fingerprint of some plants, typically by gas chromatography, methods capable of quantifying representative terpenes in herbal preparations and dietary supplements with combined high sensitivity and precision, simplicity, and high throughput are still necessary. In this study, we have explored the utility of capillary liquid chromatography (CapLC) with diode array detection (DAD) for the determination of different terpenes, namely limonene, linalool, farnesene, α-pinene, and myrcene. An innovative method is proposed that can be applied to quantify the targets at concentration levels as low as 0.006 mg per gram of sample with satisfactory precision, and a total analysis time <30 min per sample. The reliability of the proposed method has been tested by analyzing different dietary supplements of botanical origin, namely three green coffee extract-based products, two fat burnings containing Citrus aurantium (bitter orange), and an herbal preparation containing lime and leaves of orange trees.